Bayesian Psychometric Modeling. Issue 2 (3rd April 2018) - Qiao, Xin; Jiao, Hong
ABSTRACT: This article aims to review the book "Bayesian psychometric modeling" by Levy and Mislevy (2016). It provides an overview of the book content and explains the significance of Bayesian psychometric modeling issues that were explored in the book. Both strengths and weaknesses of the work are discussed. Some recommendations for revisions of the book are provided.